The document in the inheritance by the writer-experimentalist: textual peculiarities - Levytsky, Vyacheslav (Ukrainian linguistics, 2017)
The article investigates the most important trends in the formation of business papers by Oleksa Vlyzko (1908–1934). This Ukrainian writer belonged to the literary groups “Nova Heneratsiya” (“The New Generation”), “Molodnyak” (“The Offspring”), Ukrainian Union of Proletarian Writers and combined the elements of Vanguardistic and Neo-Romantic poetics into one. The aim of proposed work is determination of the standards of Ukrainian legal (official-business) style that are represented in the documents of the man of letters who gravitates to experiments in imaginative texts. The topicality of the research consists in the analysis of the manifestations of the author’s individuality in such style which is often treated as the kind of unemotional and even bureaucratic discourse. At the same time the conciousness of the follower of the play in the belles-lettres may be ‘programmed’ to expressive account in another spheres. Vlyzko’s vision of a document is interpreted in purely linguistic, biographical and textological aspects. The first of them lets to discern the emotional lexical and phraseological means, methapors, Russisms with some connotations in business papers (халтура ‘potboiler’; <...> хочу щоб <...> не махали перед моїм носом, як перед носом осла оберемком сіна “I want that <...> anyone shouldn’t wave in front of my nose like he should wave with a bottle of hay in front of a nose of a donkey”; єрунда ‘rubbish’ (Russian)). As biographical materials show, Oleksa Vlyzko liked various provocations and pranks. Those ways of behaviour were the notable factors of his linguistic communication with editors and state institutions. Finally, the rough copies of writer’s documents contain many corrections, especially fixed components and words that are crossed out. This peculiarity also testifies to the evolution of Vlyzko’s special communicative etiquette and significant idiostyle in Ukrainian legal (official-business) style. The innovatory material of the research includes the sources from Manuscript Institute at Volodymyr Ivanovych Vernadsky Ukrainian National Library. Information about the author: Vyacheslav Levytsky – PhD, Chief Civil Service Specialist (Ukraine). https://scholar.google.com.ua/citations?user=gJKpMoUAAAAJ&hl __________ References • Batsevych F. (2016) Linhvokomunikatyvni ta rytoryko-prahmatychni vymiry khudozhnoho tekstu (na materiali romanu Ivana Franka ‘Perekhresni stezhky’) [The Lingvocommunicative and Rhetoric and Pragmatic Dimensions of Imaginative Text (Based on Ivan Franko’s Novel “The Cross Paths”)]. Lviv: LNU im. I. Franka, 204 p. (in Ukrainian). • Bohush S. (2012) Mownyia asablivastsi sluzhbovykh dakumentaw Ia. Kupaly [The Linguistic Peculiarities of Official Documents by Ia. Kupala]. Proceedings of the Language – Literature – Culture: VIII International Scientific Conference (Minsk, 2012) (ed. T.Shamiakina), Minsk: Vyd. tsentr BDU, pp. 139-143 (in Belorussian). • Kotsarev O., Stakhivska Yu. (eds.) (2014) Oleksa Vlyzko: Biohrafichna dovidka [Oleksa Vlyzko: The Biographic Information]. Ukrainian avant-garde poetry (1910-1930): Anthology. Kyiv: Smoloskyp, pp. 131-133 (in Ukrainian). • Lavrinenko Yu. (2007) Oleksa Vlyzko: literaturna sylveta [Oleksa Vlyzko: the Short Literary Portrait]. The Shot up revival: anthology: 1917-1933: poetry – prose – drama – esey. Kyiv: Smoloskyp, pp. 374-377 (in Ukrainian). • Levytsky V. (2016) Vyiav aktanta v ofitsiino-dilovomu spilkuvanni [The Representations of Actant in Official Communication]. Proceedings of the Days of Science Faculty of Philosophy – 2016. Kyiv: Kyiv University, vol. 3, pp. 91-93 (in Ukrainian). • Skopnenko O.I., Tsymbaliuk T.V. (eds.) (2007) Mala filolohichna entsyklopediia [The Short Philological Encyclopedia]. Kyiv: Dovira, 2007, 478 p. (in Ukrainian). • Matsko L., Kravets L. (2007) Kultura ukrainskoi fakhovoi movy [The Culture of Professional Language]. Kyiv: Akademiia, 2007, 360 p. (in Ukrainian). • Palionis I. (1986) Ob aktualnosti problemy ‘obshcheliteraturnaia norma i funktsyonalnyie stili” [About the Topicality of the Problem “General Literary Rate and Functional Styles”]. General literary language and national styles: Collected papers. Vilnius: Mokslas, pp. 6-14 (in Russian). • Slaboshpytsky M. (2008) Veniamin literaturnoi simуі [Benjamin of Literary Family]. Kyiv: Yaroslaviv Val, 288 p. (in Ukrainian). • Tymenko L. (2007) Rozvytok leksyky ofitsiino-dilovoho styliu ukrainskoi movy na pochatku 20 st. (1917-1933) [The Development of Lexicon of Official Style of Ukrainian Language on the Beginning of 20th Century (1917-1933)] (PhD Thesis), Kyiv. 20 p. (in Ukrainian). • Tubalova I. (2011) Problemy transformatsii smysla “sovetskoho teksta” v rechevoi srede postsovetskoi derevni [The Problems of the Transformation of the Sense of “Soviet Human” in the Communicative Environment of Post-Soviet Village]. Language and culture, vol. 3, pp. 94-105 (in Russian). • Tsymbal Ya. (2007) Try “S” ukrainskoho futuryzmu: seks – sport – skandal [Three “S” of Ukrainian Futurism: Sex – Sports – Scandal]. Antyproloh : Zb. nauk. prats, prysviachenykh 60-richchiu M. Sulymy [Antyproloh: Collected papers, dedicated to the 60th anniversary of М.Sulima]. Kyiv : Stylos, pp. 383-392 (in Ukrainian).